On the importance of sectoral shocks for price-setting - Guenter W. Beck; Kirstin Hubrich; Massimiliano Marcellino (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We use a novel disaggregate sectoral euro area dataset with a regional breakdown that allows explicit estimation of the sectoral component of price changes (rather than interpreting the idiosyncratic component as sectoral as done in other papers). Employing a new method to extract factors from over-lapping data blocks, we find for our euro area data set that the sectoral component explains much less of the variation in sectoral regional inflation rates and exhibits much less volatility than previous findings for the US indicate. Country- and region-specific factors play an important role in addition to the sector-specific factors. We conclude that sectoral price changes have a 'geographical' dimension, as yet unexplored in the literature, that might lead to new insights regarding the properties of sectoral price changes.
urn:nbn:de:hebis:30-73629
Keywords: E31; E4; E5; C3; 330; Disaggregated Prices; Euro Area Regional and Sectoral Inflation; Common Factor Models; Inflation; Preisspanne; Branche; Schock; Regionale Preisstruktur; Schätzung; Eurozone